2022
DOI: 10.3389/fsufs.2021.799587
|View full text |Cite
|
Sign up to set email alerts
|

Driving Management of Novel Foods: A Network Analysis Approach

Abstract: The food industry has confronted, in recent years, numerous issues including meeting a food demand for individual well-being in a sufficient and healthy manner, also due to the effects of the world population growth. In this scenario, alternative food sources may be a key element both for their contribution to food needs and for the promotion of sustainable and innovative production patterns. These food sources, new compared to traditional food styles, have been regulated by specific European Union regulations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 103 publications
(140 reference statements)
0
1
0
Order By: Relevance
“…However, industrial food waste often comes from the parts of plants that humans usually do not eat. Thus, food made from this waste is considered a novel food, which requires safety assessment for consumption in humans [ 23 , 24 ]. In this study, we reported a randomized placebo-controlled trial to assess the clinical safety and potential efficacy of continuously repeated intake of coffee cherry pulp juice concentrate, a product made from food waste from coffee manufacturing.…”
Section: Discussionmentioning
confidence: 99%
“…However, industrial food waste often comes from the parts of plants that humans usually do not eat. Thus, food made from this waste is considered a novel food, which requires safety assessment for consumption in humans [ 23 , 24 ]. In this study, we reported a randomized placebo-controlled trial to assess the clinical safety and potential efficacy of continuously repeated intake of coffee cherry pulp juice concentrate, a product made from food waste from coffee manufacturing.…”
Section: Discussionmentioning
confidence: 99%